Policy performance evaluation from the perspective of a simple input-output transformation theory: A study on the utilization of grant and social assistance funds in Kediri city - Syahputra, Fandi Reza; Zauhar, Soesilo; Sarwono, Sarwono; Nuh, Mohammad (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate the performance of public policies regarding the utilization of grants and social assistance funds (bansos) in Kediri City, employing the input-output transformation theory. Focusing explicitly on poverty alleviation and social protection policies, this research identifies the effectiveness and efficiency of policies in enhancing community welfare. The study employs a qualitative method, conducting an in-depth analysis of primary and secondary data, supplemented by interviews with policymakers and beneficiaries. The findings reveal that although grants and social assistance funds have substantially contributed to reducing poverty rates, their implementation remains hindered by various challenges, including inefficiencies, lack of transparency, targeting inaccuracies, and the politicization of aid, especially approaching regional head elections. Furthermore, the evaluation demonstrates that the input-output approach effectively elucidates the relationship between resource allocation (input) and policy outcomes (output). Nonetheless, this approach necessitates reinforcement through stringent monitoring and oversight mechanisms to enhance accountability and transparency. This research recommends developing a more comprehensive policy evaluation model through the integration of technology-based information systems, targeted human resource training, and institutional restructuring. The study contributes theoretically to public administration scholarship, particularly within social policy evaluation, and offers practical implications for local governments in managing grants and social assistance funds with greater effectiveness and accountability.